An Assessment of the Adequacy of the Methods Of Domestic Solid Waste Management in Kisii Town, Kenya - Naftal, Mecheo O. (Advances in Social Sciences Research Journal, 2021)
Urban domestic solid waste is increasingly being generated in many urban centres including middle sized towns. In many urban areas in developing countries there’s a growing need and awakening for meeting the waste disposal for the ever increasing population. This paper examines and analyses the varied treatment and disposal methods of domestic solid waste employed in Kisii town. The specific objective of the study include: to assess the adequacy of the available management systems of handling domestic solid waste (DSW) in Kisii town. A mixed methodology approach was taken into consideration. A sample of 110 households was obtained using the multi stage stratified sampling method. Data collection methods of the sampled size involved the use of questionnaires to 110 householders and direct interviews to 2 county officers in charge of DSW and observation integrated with photography. Data analysis was carried out using methods such as use of tables and graphs through SPSS. The results indicate that the storage facilities are inadequate for the residents, the collection times are not only insufficient but also irregular, the transportation means employed are limited, and disposal and treatment of the DSW is limited to mainly open dumping at the overfilled Nyambera dumpsite. In conclusion, the management methods of the DSW are inadequate and pose severe health risks to the residents of Kisii. It is recommended that, for effective domestic solid waste management adequate bins should be provided in the town, collection should be regular and indiscriminate in all estates, recycling, re-use, reduce and energy recovery should be introduced to move from challenges to opportunities. Finally, an integrated model of integrating CBOs and private groups in management of DSW is suggested to ensure sustainable solid waste management.